2014
DOI: 10.2169/internalmedicine.53.1900
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Vasospasms of the Coronary Arteries due to Multiple Factors: An Autopsy Case

Abstract: A 41-year-old man was admitted with decompensated heart failure. Mechanical ventilation was maintained with a large dose of propofol. On day 4, significant ST elevation with complete atrioventricular block was noted, which subsequently induced cardiopulmonary arrest. Treatment with percutaneous cardiopulmonary support and therapeutic hypothermia was initiated. Emergent cardiac angiography showed simultaneous multivessel coronary spasms. Although nitroglycerin and nicorandil were ineffective, the intracoronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In Case 4, after surgical abortion under anesthesia of propofol, a childbearing woman experienced refractory angina, which was highly suspected as coronary vasospasm evidenced by classical clinical manifestations of angina and nearly normal coronary artery in angiography. Several case reports described transient coronary vasospasm based cardiac events under the administration of Propofol [25], but in our case, the first onset of angina occurred 7 days after the administration of propofol, and the following refractory relapse had no relation with propofol, indicating the little causality between propofol administration and angina. Another explanation might be as below: the surgery had injured her endometrium and disturbed the ovarian function, evidenced by the significant delay of menstruation recovery.…”
Section: Discussionmentioning
confidence: 58%
“…In Case 4, after surgical abortion under anesthesia of propofol, a childbearing woman experienced refractory angina, which was highly suspected as coronary vasospasm evidenced by classical clinical manifestations of angina and nearly normal coronary artery in angiography. Several case reports described transient coronary vasospasm based cardiac events under the administration of Propofol [25], but in our case, the first onset of angina occurred 7 days after the administration of propofol, and the following refractory relapse had no relation with propofol, indicating the little causality between propofol administration and angina. Another explanation might be as below: the surgery had injured her endometrium and disturbed the ovarian function, evidenced by the significant delay of menstruation recovery.…”
Section: Discussionmentioning
confidence: 58%
“…"Since the mechanism of vasodilation by "Fasudil" is completely different from that of nitrates, additional administration of "Fasudil" after nitrates could promote an additive effect in coronary vasodilation" [45]. "Although numerous case reports strongly suggest the utility of intracoronary administration of fasudil in patients with multi-resistant or refractory coronary spasms" [46][47][48], no randomized controlled trial or observational study has objectively demonstrated that the Fasudil is superior to conventionally used vasodilators, such as nitrates and nicorandil in the relief of coronary artery spasms. This promising therapeutic class is not recommended in European guidelines.…”
Section: Rho-kinase Inhibitorsmentioning
confidence: 99%
“…[ 6 ] In this context, elevated levels of serum eicosapentaenoic acid (EPA) and DHA before PCI resulted in the inhibition of I/R injury. [ 7 ] Previous studies have also suggested that ω ‐3 PUFAs suppress inflammation [ 8 ] and arrhythmias, [ 9 ] reduce platelet aggregation, [ 10 ] decrease resultant ischemic oxidative injury, [ 11 ] and inhibit apoptotic signaling. [ 12 ] The major advantage of dietary administration is the noninvasive nature of administration; however, the provision of cardioprotection by ingested ω ‐3 PUFAs remains a more complex scenario than intravenous administration or pericardial perfusion.…”
Section: Introductionmentioning
confidence: 99%